2021
DOI: 10.1016/j.tracli.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Positive direct antiglobulin test in COVID-19 patients: Decision-making process

Abstract: In this unprecedented crisis of severe acute respiratory syndrome coronavirus 2 and its associated coronavirus disease 2019 (COVID-19), polymerase chain reaction and then serological testing platforms have been massively developed to face the important screening demand. Polymerase chain reaction and serological testing platforms are not the only actors impacted by the crisis, transfusion services are facing important difficulties. A positive direct antiglobulin test is frequently observed for patients encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Almost all patients in these studies showed positive DAT with IgG, C3d, and IgG+C3d antibodies. These studies also indicate a high prevalence of DAT positivity in patients with COVID-19, confirming that cases of hemolysis tend to present with IgG+C3d or C 3 d [10] , [11] . However, the mechanism underlying DAT positivity in patients with COVID-19 remains unclear.…”
Section: Introductionsupporting
confidence: 61%
“…Almost all patients in these studies showed positive DAT with IgG, C3d, and IgG+C3d antibodies. These studies also indicate a high prevalence of DAT positivity in patients with COVID-19, confirming that cases of hemolysis tend to present with IgG+C3d or C 3 d [10] , [11] . However, the mechanism underlying DAT positivity in patients with COVID-19 remains unclear.…”
Section: Introductionsupporting
confidence: 61%
“…Due to the COVID-19 outbreak, many chronic patients and elective surgical procedures have been postponed to create spaces for the hospitalization of COVID-19 patients. The need for transfusion support in COVID-19 patients was not known (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%